(untitled) (World Bulletin of Management and Law, 2024)
With the advancement of medicine, artificial insemination emerged as a process performed by specialized doctors to deal with the problem of infertility among spouses. In this process, an ovum is fertilized with semen, where the fertilization process is implemented in an artificial environment. Then, artificial insemination occurs as the fertilized ovum is implanted in the wife’s womb. Despite the advantages of this process in dealing with the problems of infertility, it is just like all other medical procedures, as it may cause harm to the wife and husband during the primary procedures of fertilization, during artificial insemination, or even after the fertilization process. Therefore, the civil medical responsibility of this process should be determined, and the specialized medical centres should be monitored cautiously to avoid any medical errors and protect semen from careless procedures and the mixing of breeds as well as the consequences. Also, the concerned doctor should maintain confidentiality, given the sensitivity and privacy of these processes. These processes should also be implemented in well-known specialized medical centres under the supervision of the Ministry of Health.